2020
DOI: 10.25056/jcm.2020.4.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Internet-of-things nail-printing technology using non-face-to-face contact

Abstract: Background: With the spread of coronavirus disease-19 , face-to-face contact in business and educational hubs has decreased. This is especially true for the beauty industry, where long-term contact with operators and customers is required. Therefore, the emergence of new alternative business models is essential. Objective:The purpose of this study is to apply nonfacing and real-time three-dimensional (3D) nail-printing systems to cosmetic industries, educational institutions, and educational systems. Three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In this study, printing technology using the untact concept has been applied to and demonstrated in the field of nail art. Since the introduction of the first remote 3D nail printing technology, many experiments have been conducted and controlled online between Korea and the United States, and the untact IoT technology is currently in the commercialization stage [20][21][22][23]. It is crucial to examine and develop healthy and stable inks suitable for such applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, printing technology using the untact concept has been applied to and demonstrated in the field of nail art. Since the introduction of the first remote 3D nail printing technology, many experiments have been conducted and controlled online between Korea and the United States, and the untact IoT technology is currently in the commercialization stage [20][21][22][23]. It is crucial to examine and develop healthy and stable inks suitable for such applications.…”
Section: Introductionmentioning
confidence: 99%